Любовь Бешеного: [роман] / Виктор Доценко - Доценко Виктор Николаевич (Вагриус, 1997)
Экземпляры: ф15 (20190515) / Инвентарный номер: 194266 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 71 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6